Pengembangan aplikasi simpelbik untuk meningkatkan hasil belajar kompetensi keahlian siswa tata kecantikan SMKN 3 Kota Bengkulu - Selvia Tristianty Hidajat; Prahasti (Ikatan Bimbingan dan Konseling Sekolah)
This research aimed to develop a media of guidance and counseling service by using an application of sistem pakar. The method was used in this research is research and development with the method of ADIIE design. The product is developed are a guidance and counseling service media, that is sistem pakar application by using visual basic 0,6. The result of this research is a product of guidance and counseling media by using sistem pakar application to help improving score of SMKN 3 Kota Bengkulu students which has been developed according to learning media developing procedure including need analysis, design, development, implementation and evaluation. This application was effective to increase learning score of student’s competent skill majoring of beauty in SMKN 3 Kota Bengkulu.